High temperature tensile test and creep rupture strength prediction of T92/Super304H dissimilar steel weld joints. (2014) - Bai, X. L.; Zhang, Q.; Chen, G. H.; Wang, J. Q.; Liu, J. J.; Yu, X. H.; Hua, J.; Zhang, J. H.; Tang, W. M.
Abstract : After short term tensile test at 823–923 K, microstructure, fractography and fracture mechanism of the T92/Super304H dissimilar steel weld joints were studied. In the high temperature tensile process, the fracture location of all joints is in the T92 base metal; however, the fracture mechanism of these joints changes from a normal mode to a shear mode with the increase of the temperature. Moreover, an equation of the creep rupture strength related to the short term tensile strength of the joints was firstly derived in terms of the Goldenberg model. And then the creep rupture strength of the joints was obtained,  = 42·7 MPa.